The Wahls protocol : how I beat progressive ms using Paleo principles and functional medicine - Wahls, Terry L. (Avery, 2014)
" An integrative approach to healing chronic autoimmune conditions by a doctor, researcher, and sufferer of progressive multiple sclerosis (MS) whose TEDx talk is already a web sensation Like many physicians, Dr. Terry Wahls focused on treating her patients' ailments with drugs or surgical procedures-until she was diagnosed with multiple sclerosis (MS) in 2000. Within three years, her back and stomach muscles had weakened to the point where she needed a tilt-recline wheelchair. Conventional medical treatments were failing her, and she feared that she would be bedridden for the rest of her life. Dr. Wahls began studying the latest research on autoimmune disease and brain biology, and decided to get her vitamins, minerals, antioxidants, and essential fatty acids from the food she ate rather than pills and supplements. Dr. Wahl's adopted the nutrient-rich paleo diet, gradually refining and integrating it into a regimen of neuromuscular stimulation. First, she walked slowly, then steadily, and then she biked eighteen miles in a single day. In November 2011, Dr. Wahls shared her remarkable recovery in a TEDx talk that immediately went viral. Now, in The Wahls Protocol, she shares the details of the protocol that allowed her to reverse many of her symptoms, get back to her life, and embark on a new mission: to share the Wahls Protocol with others suffering from the ravages of multiple sclerosis and other autoimmune conditions"--